2018
DOI: 10.1080/01616412.2018.1453980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different frequencies of repetitive transcranial magnetic stimulation in stroke patients with non-fluent aphasia: a randomized, sham-controlled study

Abstract: LF-rTMS and HF-rTMS are both beneficial to the recovery of linguistic function in patients with post-stroke non-fluent aphasia. LF-rTMS produced immediate benefits that persisted long-term, while HF-rTMS only produced long-term benefits. In addition, the benefits produced with LF-rTMS were more marked than those produced by HF-rTMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 41 publications
1
65
0
1
Order By: Relevance
“…We also found that the application of LF-rTMS to the right pIFG displayed apparently beneficial changes in WAB-AQ, spontaneous speech, and repetition. This result is consistent with previous studies that showed that LF-rTMS over the right prIFG exhibited superior performance in spontaneous speech, comprehension, repetition, naming, and AQ in nonfluent aphasia [3, 8, 22, 23]. However, in our study, only small changes were observed in the recovery of naming ability between pre- and posttreatment with rTMS for global aphasia.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also found that the application of LF-rTMS to the right pIFG displayed apparently beneficial changes in WAB-AQ, spontaneous speech, and repetition. This result is consistent with previous studies that showed that LF-rTMS over the right prIFG exhibited superior performance in spontaneous speech, comprehension, repetition, naming, and AQ in nonfluent aphasia [3, 8, 22, 23]. However, in our study, only small changes were observed in the recovery of naming ability between pre- and posttreatment with rTMS for global aphasia.…”
Section: Discussionsupporting
confidence: 93%
“…Mounting studies have demonstrated that inhibitory low-frequency repetitive transcranial magnetic stimulation (LF-rTMS) (≤1 Hz) over the unaffected hemisphere can improve language function in poststroke aphasic patients with left-hemispheric lesions [36]. Language functional recovery occurs because of compensatory facilitation of the left hemisphere following the reduction of interhemispheric inhibition by suppressive LF-rTMS.…”
Section: Introductionmentioning
confidence: 99%
“…Also included in the motor relearning interventions were the 208 trials on Activities of Daily Living (ADL), 108 and 51 trials on gait and mobility, respectively. These neurorehabilitation techniques include innovatively high technology interventions such as robotic therapy ( 11 50 ), transcranial direct current stimulation ( 16 , 29 , 51 64 , 344 ), transcranial magnetic stimulation ( 66 94 ), functional electrical stimulation ( 95 112 ), virtual reality ( 113 129 ), and video game ( 130 132 ). Many of these trials reported “within-group” improvement in motor functioning outcomes in both intervention and control groups (usually conventional therapy) with no “between-group differences” in these outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…[58] In addition, most survivors suffer from server impairments, such as limbs paralysis or weakness, depression, bladder or bowel disorders, and aphasia. [920] Therefore, timely and effective managements are very important for the CH survivors.…”
Section: Introductionmentioning
confidence: 99%